Determination of the kinetics of the process of pumpkin seeds vibrational convective drying - Kaletnik, Grigory; Tsurkan, Oleh; Rimar, Tetiana; Stanislavchuk, Oksana (Eastern-European Journal of Enterprise Technologies, 2020)
Experimental studies of the drying process of high-moisture pumpkin seeds in a vibrating dryer are carried out. The research is caused by the need to solve the problem of fast and high-quality post-harvest treatment with minimal cost. Existing technologies and equipment do not ensure high performance of the drying process in the post-harvest period or carry it out with significant expenses of time and resources. The main objective of the study is to determine the rational parameters of the process and equipment for drying pumpkin seeds. As a result of the experimental studies of the kinetics of pumpkin seeds vibrational convective drying, rational process parameters were obtained, i. e. the maximum allowable temperature of the drying agent is tda=50 °С, which corresponds to the maximum allowable heating temperature of seeds th2=46.7 °С. At this temperature, the grain retains conditional values of germination ability and energy. The maximum allowable temperature is 0.3 °C lower than the maximum allowable heating temperature for pumpkin seeds. The results of the study of the intensification of vibration exposure indicate a direct relationship between the vibration frequency of the drying chamber and drying duration: the higher the frequency, the greater the intensity of vibration-convection drying, as well as a reduction in drying duration with increasing vibration amplitude. The obtained results confirm the feasibility of using a filtration-convective vibrating dryer, which ensures compliance with rational drying parameters, i. e. temperature and speed of the drying agent, amplitude, frequency, and filling of the working chamber. The combination of these parameters allows drying the seed material with minimal cost and maintaining its high quality